FACTORS OF INFLUENCE ON EMPLOYMENT IN SMALL AND MEDIUM-SIZED BUSINESS IN UKRAINE - I. V. Zhurakovska; R. V. Sydorenko; T. O. Shmatkovska; I. I. Brodska (Фінансово-кредитна діяльність: проблеми теорії та практики)
In small and medium-sized businesses, the vast majority of the entire officially employed able-bodied population of the country is employed.